MENINGKATKAN KEMAMPUAN ADVANCED MATHEMATICAL THINKING DENGAN MENGGUNAKAN MODEL PEMBELAJARAN MATEMATIKA KNISLEY PADA MATA KULIAH TRIGONOMETRI - Nelly Fitriani; Puji Nurfauziah (IKIP Siliwangi, 2020)
This study aims to examine the improvement of Advanced Mathematical Thinking in students whose learning uses the Knisley Mathematical model compared to those using ordinary learning. The research method used is quantitative with Pretest-Postest-Only design, with the instrument used is the Advanced Mathematical Thinking test instrument with 3 categories of questions. Learning is carried out applied to one of the courses at the basic level, Trigonometry. The results obtained from this study are students whose learning using the Knisley mathematical model in Trigonometry courses is better improved than those using ordinary learning, the most prominent results are in the ability of representation and the results that still tend to be low are in the ability of abstraction.